Social Maturity Among Tribal Adolescents: A Study of Gender Differences and Family Structures - Adhikari, Pushpa (Far Western Review, 2024)
India is characterised by a diverse tapestry of castes, classes, religions, and languages. As a democratic nation, Indiaprovides opportunities for the development of all its citizens. However, certain groups remain marginalized, particularly tribal communities, who often follow traditional or primitive lifestyles and reside in remote regions of the country. Their interactions with other social groups are limited, which further contributes to their isolation from the mainstream. It is crucial for governments whether central or state to integrate these communities into the mainstream. In line with this goal, the researcher intends to evaluate the social maturity of tribal students and examine how gender and family type influence this aspect among students enrolled in government schools in Udham Singh Nagar district of Uttarakhand. A sample of 100 tribal students (54 girls and 46 boys) was randomly selected for this study. The findings indicate that the majority of tribal students exhibit an average level of social maturity. Notably, the impact of gender on social maturity was found to be statistically significant, revealing that girls encounter greater challenges in social adjustment compared to boys. In the dimensions of Cooperation, Social Commitment, and Openness to Change, girls scored lower than their male counterparts. Conversely, the family type did not show a significant effect on the students’ social maturity. This study underscores the necessity for society to pay special attention to tribal communities, particularly focusing on the social development of tribal girls.